Construction and application of a model for drainage via directional boreholes against water hazards in deep vertical shafts - Chunhu ZHAO; Mingcheng ZHU; Yadong JI; Shidong WANG; Wenzhong ZHANG; Kaipeng ZHU; Yingfeng LIU; Hongbo SHANG; Chaofeng LI; Min FAN; Kai LI (Meitian dizhi yu kantan)
BackgroundVertical shafts are typically employed in the deep mining areas of Jurassic coalfields in western China. However, the direct exposure of extremely thick Cretaceous aquifers frequently leads to significant water inflow in shafts. Meanwhile, the continuous sand-carrying water inflow and scouring in vertical shafts pose serious safety hazards to the overall quality of shaft walls. MethodsIn underground water exploration and discharge boreholes, water outlets are below the floors of aquifers to be drained. This allows unpowered water discharge. In other words, water can flow out naturally. By fully leveraging this advantage, combined with the favorable condition of spatial trajectory control during surface directional drilling, this study investigated the deep vertical shafts in a production mine in the Binchang mining area of the Huanglong coal base within a Jurassic coalfield in western China. Accordingly, this study proposed a nondestructive technical approach to controlling water in extremely thick sandstones in deep vertical shafts based on advance drainage through directional drilling. Using the COMSOL Multiphysics finite element numerical simulation platform, this study conducted numerical processing of Darcy seepage overflow boundaries and permeable layer boundaries to address the challenge that the structures and natural drainage processes of directional boreholes cannot be scientifically described using the passive pumping model of surface vertical wells. Accordingly, this study established a numerical simulation model of the groundwater system integrating deep-seated, thick, water-rich sandstone aquifers, surface directional boreholes for advance drainage, and deep vertical shafts. Using this model, this study quantitatively explored the changes in water inrush and water reduction effects in vertical shafts under the condition of advance regional drainage via surface directional boreholes.Results and ConclusionsThe simulation results of water inrush in the shafts studied indicate that the water inflow in drainage boreholes ZX1‒ZX4 was 34 m3/h, 27 m3/h, 38 m3/h, and 42 m3/h, respectively, as determined by the numerical processing of the four drainage boreholes and the integral of groundwater flow velocity around borehole and shaft walls. Meanwhile, the water inflow of the main and auxiliary vertical shafts decreased from 21.5 m3/h and 22 m3/h to 5.82 m3/h and 4.43 m3/h, respectively. Therefore, water reduction in the vertical shafts studied can be achieved by advance drainage via four surface directional boreholes, with the water reduction effect satisfying the safety and quality requirements for shafts. The results of this study will provide a reference for the scientific management, analysis, and calculation against water hazards in shafts in deep mines within Jurassic coalfields in western China.